Relationship of Burnout with Mental Stress, Job Satisfaction among Nurses - Shahzad, Muhammad; Nafees, Mehreen; Khizer, Sumbal (Biological and Clinical Sciences Research Journal, 2025)
Nurses frequently experience high levels of stress due to demanding workloads, emotional strain, and complex healthcare environments, which may contribute to burnout and reduced job satisfaction. Understanding the interplay between mental stress, burnout, and job satisfaction is essential to improving nursing wellbeing and patient care quality. Objective: To evaluate the relationship between mental stress and nurses’ burnout levels and job satisfaction. Methodology: Nurses working in the Nursing Department of the tertiary care hospital were cross-sectionally analyzed from April 2023 to April 2024. A total of 90 nurses working in the hospital for 1 year or more were included in the study.Personal data of nurses including gender and marital status were noted. Mental stress was evaluated by translated version of 28-item questionnaire designed by Bradbury and Graves.Burnout was assessed by 22-item questionnaire designed by Maslash and Jackson.Job satisfaction was determined by 39-item questionnaire designed by Visoki and Chrome on 5 dimensions; job component, promotion, supervisor, payment, colleague. Results: A significant F ratio of 44.818 was recorded between burnout and mental stress. The R2 value showed that a 0.09% change in burnout level can be predicted by emotional intelligence. There was also a significant F ratio of 772.797 between job satisfaction and relationship management, a component of emotional intelligence. A 0.61% change in job satisfaction could be predicted by relationship management.Burnout was significantly associated to all components of emotional intelligence; relationship management (0.363), social awareness (0.213), self-management (0.148) and self-awareness (0.147). Conclusion: Emotional intelligence has a significant impact on level of burnout in nurses with a high EI leading to reduced burnout.